Recycling of polyethylene terephthalate (PET) plastic bottle wastes in bituminous asphaltic concrete. Issue 1 (31st December 2016) - Sojobi, Adebayo Olatunbosun; Nwobodo, Stephen Emeka; Aladegboye, Oluwasegun James
Abstract: This research sheds light on the concept of eco-friendly road construction which comprises eco-design, eco-extraction, eco-manufacturing, eco-construction, eco-rehabilitation, eco-maintenance, eco-demolition, and socioeconomic empowerment. It also revealed the challenges being faced in its adoption and the benefits derivable from its application. Furthermore, the effects of recycling PET plastic bottle wastes produced in North Central Nigeria in bituminous asphaltic concrete (BAC) used in flexible pavement construction were also evaluated. The mix design consists of 60/70 penetration-grade asphaltic concrete (5%), 68% coarse aggregate, 6% fine aggregate, and 21% filler using the dry process at 170°C. The optimum bitumen content (OBC) for conventional BAC was obtained as 4% by weight of total aggregates and filler. Polymer-coated aggregate (PCA)-modified BAC seems preferable because it has the potential to utilize more plastic wastes with a higher optimum plastic content (OPC) of 16.7% by weight of total aggregates and filler compared to that of 9% by weight of OBC achieved by PMB-BAC. For both PMB- and PCA-modified BAC, an increase in air void, void in mineral aggregate, and Marshall stability were observed. Eco-friendly road construction which recycles PET wastes should be encouraged by government considering its potential environmental and economic benefits.